2012
DOI: 10.1021/la301094h
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Bilayers Covalently Anchored to Carbon Nanotubes

Abstract: The unique physical and electrical properties of carbon nanotubes make them an exciting material for applications in various fields such as bioelectronics and biosensing. Due to the poor water solubility of carbon nanotubes, functionalization for such applications has been a challenge. Of particular need are functionalization methods for integrating carbon nanotubes with biomolecules and constructing novel hybrid nanostructures for bionanoelectronic applications. We present a novel method for the fabrication o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 68 publications
1
13
0
Order By: Relevance
“…The peak in the 240 °C - 270 °C region is primarily attributed to PC as it is unique to the PC-coated samples and is consistent with previous studies of PC pyrolysis. 39 The weight loss from a corresponding uncoated SiNP was subtracted from the coated sample to determine the amount of PC on the SiNP (Table 2). Attempts at lipid coating SiNPs with 100% ODTS functionalization resulted in rapid aggregation in aqueous solutions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The peak in the 240 °C - 270 °C region is primarily attributed to PC as it is unique to the PC-coated samples and is consistent with previous studies of PC pyrolysis. 39 The weight loss from a corresponding uncoated SiNP was subtracted from the coated sample to determine the amount of PC on the SiNP (Table 2). Attempts at lipid coating SiNPs with 100% ODTS functionalization resulted in rapid aggregation in aqueous solutions.…”
Section: Resultsmentioning
confidence: 99%
“…Sodium dithionite, which quenches the NBD fluorescence by chemically reducing the dye, 39 was added to the PC-coated SiNPs. The fluorescence of each sample was measured and compared to its initial fluorescence.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, no further thickness increase of the 1D template is required, compared to e.g. thinner single-walled CNTs [21,41]. Due to Brownian motion the NW moves inside its fluid environment variantly leaving and entering the focus plane (see movie 1 in ESI available at stacks.iop.org/Nano/24/355601/mmedia).…”
Section: Lipid Bilayers Around Sinwsmentioning
confidence: 99%
“…Longer incubation times will probably increase the chances for SLB formation on uncoated NWs. According to Dayani et al [41], 1D templates of comparable diameter with a lipid bilayer shell are stable in buffer solution for 60 days. Moura et al [42] reported single stabilization of a colloidal solution of lipid coated silica particles when intact single bilayers cover the surface with a saturated phosphocholine density.…”
Section: Lipid Bilayers Around Sinwsmentioning
confidence: 99%
“…Several approaches have been developed to integrate nanoparticles with polymeric species. These include physical wrapping, chemical grafting, and in situ growth of nanoparticles in polymeric media . Noncovalent, or physical functionalization of nanoparticles may utilize strong polymer–particle interactions such as electrostatics or π−π stacking, for example in the case of conjugated polymers or pyrene derivates on graphene and carbon nanotubes (CNTs) .…”
Section: Introductionmentioning
confidence: 99%